Management of the Upper Airway in Cystic Fibrosis - Illing, Elisa A. (Curr Opin Pulm Med, 2014)
PURPOSE OF REVIEW: Upper airway disease engenders significant morbidity for patients with cystic fibrosis and is increasingly recognized as having a much greater role in pulmonary outcomes and quality of life than originally believed. Widespread disparate therapeutic strategies for cystic fibrosis chronic rhinosinusitis underscore the absence of a standardized treatment paradigm. This review outlines the most recent evidence-based trends in the management of upper airway disease in cystic fibrosis. RECENT FINDINGS: The unified airway theory proposes that the sinuses are a focus of initial bacterial colonization which seeds the lower airway and may play a large role in maintaining lung infections. Mounting evidence suggests more aggressive treatment of the sinuses may confer significant improvement in pulmonary disease and quality of life outcomes in cystic fibrosis patients. However, there is a lack of high-level evidence regarding medical and surgical management of cystic fibrosis chronic rhinosinusitis that makes generalizations difficult. SUMMARY: Well designed clinical trials with long-term follow-up concerning medical and surgical interventions for cystic fibrosis sinus disease are required to establish standardized treatment protocols, but increased interest in the sinuses as a bacterial reservoir for pulmonary infections has generated considerable attention.